2016
DOI: 10.1158/0008-5472.can-15-2298
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated Metabolites of Hydroxybutyric Acid Serve as Diagnostic and Prognostic Biomarkers of Ovarian High-Grade Serous Carcinomas

Abstract: Ovarian cancer is a heterogeneous disease of low prevalence, but poor survival. Early diagnosis is critical for survival, but it is often challenging because the symptoms of ovarian cancer are subtle and become apparent only during advanced stages of the disease. Therefore, the identification of robust biomarkers of early disease is a clinical priority. Metabolomic profiling is an emerging diagnostic tool enabling the detection of biomarkers reflecting alterations in tumor metabolism, a hallmark of cancer. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 43 publications
3
92
0
Order By: Relevance
“…Increased levels of long chain fatty acids were a commonly reported finding in serum and tissue of OC. Elevated palmitate, myristate and oleate concentrations were commonly reported in serum, ascitic fluid, and metastatic OC tissue (Guan et al 2009; Fong et al 2011; Shender et al 2014; Hilvo et al 2015). Further, a recent study by Buas et al used lipidomics profiling and identified 17 metabolites including glycerolipids and glycerophospholipids that were decreased in OC cases relative to controls (Buas et al 2016).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Increased levels of long chain fatty acids were a commonly reported finding in serum and tissue of OC. Elevated palmitate, myristate and oleate concentrations were commonly reported in serum, ascitic fluid, and metastatic OC tissue (Guan et al 2009; Fong et al 2011; Shender et al 2014; Hilvo et al 2015). Further, a recent study by Buas et al used lipidomics profiling and identified 17 metabolites including glycerolipids and glycerophospholipids that were decreased in OC cases relative to controls (Buas et al 2016).…”
Section: Resultsmentioning
confidence: 97%
“…Increased lysophosphatidic acid (LPA) levels were reported in urine and ascitic fluid in OC patients (Shender et al 2014; Zhang et al 2013). Ceramides and gangliosides were also increased in the serum and ascitic fluid of OC patients (Fan et al 2012; Shender et al 2014; Ke et al 2015; Hilvo et al 2015). Increased levels of long chain fatty acids were a commonly reported finding in serum and tissue of OC.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…3-hydroxybutyrate was one of the metabolites responsible for the differences in spectral patterns. These results were recently confirmed by mass spectrometry that detected accumulation of hydroxybutyric acid metabolites in ovarian cancer patient serum and tumor tissues (Hilvo et al 2016). Studies using 1 H NMR to explore ovarian cancer MA have been previously published (Bala et al 2008; Vettukattil et al 2013).…”
Section: Discussionmentioning
confidence: 58%